Managing Malaysia-Indonesia relations post-Mahathir years - Md Khalid, Khadijah; Yacob, Shakila (2009)
This paper argues that Malaysia-Indonesia relations have become increasingly problematic and difficult to manage in a more liberal post-Mahathir era. Whilst government-to-government relations between the two countries have been testy or times even tumultuous over the past five decades or so, it is the recent deterioration in people-to-people relations, meaning the perceptions and attitudes that each nations'citizens have of each other, which is now a major cause of concern and the contention of this paper. Malaysia under new leadership, is very likely to be increasingly inward-looking, with Najib Razak seeking to gain legitimacy against the growing influence of the opposition coalition led by Anwar Ibrahim, and hence bilateral relations with Indonesia will eventually take a back seat. In effect, Malaysia's relationship with its most important ASEAN neighbour is facing significant challenges with growing domestic problems in both countries exacerbated by the current global economic uncertainties.